Investing in Infrastructure : Harnessing Its Potential for Growth in Sri Lanka - Biller, Dan (Washington, DC: World Bank, 2013)
The report starts with an overview and introduces the main findings. It addresses major constraints, instruments, and outcomes important to unleash the potential of infrastructure investments and policy fine-tuning. Chapter one discusses the infrastructure and growth nexus, given the country's macroeconomic scenario. It examines the long-term sustainability, particularly considering the Mahinda Chintana's high infrastructure investment targets, and how the country can achieve its high economic growth targets, given its historical and current investment levels. Chapter two argues that the two principal drivers of sustained high economic growth and productive employment are: (a) international competitiveness that results in export-led growth; and (b) urbanization that facilitates productive economic activity. Chapter three reviews key infrastructure sectors to identify the regulatory issues that need to be addressed and estimate the needed investment. Redressing infrastructure constraints, however, cannot be piecemeal and product specific. Instead, a sector-wide approach is needed. In light of the large investment requirement and high public debt and deficit, chapter four discusses the potential of public-private partnership in infrastructure delivery and supportive regulatory reform. Finally, chapter five concludes the analysis, summarizing major highlights.